Effects of Active Review and Practice-Invention Strategies on Students’attitude to, Achievement and Process Skills in Basic Science in Oyo State (2015)
Junior secondary school students‟ achievement in Basic Science in Oyo State seems not to be encouraging, a trend attributed partly to persistent usage of teacher-centered instructional methods. This necessitates the adoption of students-centered instructional strategies such as the active review and practice-invention strategies. The effectiveness of these two instructional strategies in the teaching of Basic Science has however not been properly documented. This study, therefore, investigated the effects of Active Review (ARIS) and Practice-invention (PiIS) Instructional strategies on students‟ attitude to, and achievement and process skills in Basic Science in Oyo State. The moderator effects of Parent Educational Background (PEB) and gender were also examined. The study adopted a pretest-posttest, control group, quasi experimental design with a 3x3x2 factorial matrix. Oyo North senatorial district was purposively selected due to the observed low performance of students in Basic Science in the area. Nine Junior Secondary Schools (JSS) were randomly selected from the district, while nine intact classes of JSS II student participants were randomly assigned as follows: ARIS (131), PiIS (125) and control (131) groups. The six instruments used were Basic Science Achievement Test (r =Interrater) r = 0.80), Basic Science Attitude Scale (r = 0.86), Basic Science Process Skills Rating Scale (r = 0.76), and instructional guides for ARIS (Scott‟s π = 0.74, PiIS (π =0.76) and conventional (π =0.78) strategies. Seven null hypotheses were tested at 0.05 level of significance. Data were analysed using Analysis of Covariance and Scheffe post-hoc test. Treatment had a significant main effecton achievement (F(2, 369) = 35.25;η2= 0.16), attitude (F(2, 369) = 13.30;η2= 0.07) and science process skills (F(2,369) = 29.40;η2= 0.14). Students in the PiIS group ( =14.69) performed better than those in ARIS( =14.62) and control ( =13.08) groups. Also, they had better attitude ( =53.64) than those in ARIS ( =51.11) and control ( = 45.28). However, participants in ARIS performed better in process skills (=12.43) than those in PiIS( =11.29) and control ( =6.24).Gender had a significant main effect on achievement (F(1, 369) = 5.67;η2= 0.02), with the female performing better ( =14.48) than their male counterparts ( =13.75). The main effect of PEB was not significant, but two-way interaction effect of gender and PEB on achievement in Basic Science was significant (F(2, 369) = 5.560;η2= .03). The female students from low PEB ( =14.87) did better than their male counterparts ( =13.22). The two-way interaction effect of treatment and gender, as well as treatment and PEB were not significant. Also, the three-way interaction effect of treatment, gender and PEB was not significant. Active review and practice-invention strategies enhanced student‟s achievement in process skill and attitude to Basic Science in Oyo State. Therefore, these strategies should be adopted in teaching Basic Science to junior secondary schools students.